2020
DOI: 10.1007/978-3-030-46147-8_35
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Gaussian Processes

Abstract: We propose deep convolutional Gaussian processes, a deep Gaussian process architecture with convolutional structure.e model is a principled Bayesian framework for detecting hierarchical combinations of local features for image classication. We demonstrate greatly improved image classication performance compared to current Gaussian process approaches on the MNIST and CIFAR-10 datasets. In particular, we improve CIFAR-10 accuracy by over 10 percentage points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Gaussian Processes (GPs) with Radial Basis Function Kernels (RBF) [52] and other forms of comparative strategy create consistency overall and allow for a limitless quantity of basic functions, but these are rarely used, even though some past research has demonstrated that it can show promise [53].…”
Section: Forecastingmentioning
confidence: 99%
“…Gaussian Processes (GPs) with Radial Basis Function Kernels (RBF) [52] and other forms of comparative strategy create consistency overall and allow for a limitless quantity of basic functions, but these are rarely used, even though some past research has demonstrated that it can show promise [53].…”
Section: Forecastingmentioning
confidence: 99%
“…We focus on data-driven beamforming based mmWave fingerprinting for outdoor localization. Motivated by our prior work on CSI image-based localization [11,17], we also create mmWave beamforming images as fingerprints, which can be effectively handled by the DCGP model [16] to estimate location. DCGP integrates the convolutional structure and Gaussian process in a Bayesian framework, which can effectively extract hierarchical features from 2-D beamforming images to improve the robustness of localization performance.…”
Section: Constructing Beamforming Imagesmentioning
confidence: 99%
“…In addition, we construct the layers by using convolutions of patch response functions g l c : R h l−1 ×w l−1 ×C l−1 → R over the input one patch at a time, which can build the next layer representation. The C patch responses at each of the first L − 1 layers are considered as independent GPs with shared prior [16], where each patch response is defined by…”
Section: Training Deep Convolutional Gaussian Processmentioning
confidence: 99%
See 2 more Smart Citations